Multifrequency dielectric mapping of fixed mice colon tissues in cell culture media via scanning electrochemical microscopy - Vyas, Varun; Kotla, Niranjan G.; Rochev, Yury; Poudel, Anup; Biggs, Manus (Frontiers in Bioengineering and Biotechnology, 2023)
Alternating current scanning electrochemical probe microscope (AC-SECM) is a powerful tool for characterizing electrochemical reactivity of surfaces. Here, perturbation in the sample is induced by the alternating current and altered local potential is measured by the SECM probe. This technique has been used to investigate many exotic interfaces like live cells, tissues, corrosive degradation of various metallic surfaces, etc. In principle, AC-SECM imaging is derived from electrochemical impedance spectroscopy (EIS) which has been used for a century to describe interfacial and diffusive behaviour of molecules in solution or on a surface. Increasingly bioimpedance centric medical devices have become an important tool to detect evolution of tissue biochemistry. Predictive implications of measuring electrochemical changes within a tissue is one of the core concepts in developing minimally invasive medical devices. In this study, cross sections of mice colon tissue were used for AC-SECM imaging. 10 micron sized platinum probe was used for two-dimensional (2D) tan δ mapping on histological sections at a frequency of 10 kHz, Thereafter, multifrequency scans were performed at 100 Hz, 10 kHz, 300 kHz, and 900 kHz. Tan delta mapping of mice colon revealed microscale regions within a tissue possessing a discrete tan δ signature. This tan δ map is an immediate measure of physiological conditions in biological systems. Multifrequency scans highlights subtle changes in protein or lipid composition as a function of frequency which was recorded as loss tangent maps. Impedance profile at different frequencies can also be used to identify optimal contrast for imaging and extracting the electrochemical signature specific for a tissue and its electrolyte.